Penerapan Asas Kebebasan Berkontrak Dalam Pembuatan Perjanjian Outsourcing Dan Perjanjian Kerja Waktu Tertentu - Johan Rofi; Udin Narsudin; Zulkarnain Koto (Postgraduate of Jayabaya University, 2017)
Implementation of outsourcing involves 3 (three) parties namely labour providers, labour outsourcing companies, and labour itself. Therefore, the need for a regulation so that the parties involved no one is harmed, especially outsourcing workforce. The problem of this thesis is how the practice of outsourcing agreement for certain time in Bank BRI still causing uncertainty to employees and how the legal implication of its workers’ status null and void, pursuant to Article 15 KEP.100/MEN/VI/2004, then the status of employees will be the UTWA (Uncertain Time Working Agreement) or permanent worker for the company of the service user. The results of this study indicate that the Agreement that one of his party has a predominantly dominant position is expected to provide a balanced portion in seeking maximum benefit from the existence of an outsourcing agreement. Rights and obligations show the legal relationship between the company with the workforce, where both parties are jointly bound in the agreement of work in mutual agreement. Unauthorized termination of employment, therefore the contents and terms of the employment agreement between the parties must be made in balance with the agreement of the parties to determine the content, and the terms of the agreement. So that between the rights and obligations between the party become clear and balanced with a balanced portion and has become an agreement for the parties in making the agreement.